Effect of Inclusion of Garlic (Allium sativum) as Feed Additive on Growth and Carcass Characteristics of Japanese Quail - Bhavani, M. Durga (Indian Journal of Animal Nutrition, 2021)
One hundred and fifty, day-old quail chicks randomly distributed to five dietary treatments each with three replicates of ten quails, were offered broiler quail diets (starter and finisher) to meet the nutrient requirements (ICAR, 2013). During the experiment, dried garlic powder (GP) was included at 0.0% (T1: Control), 0.50% (T2), 1.0% (T3), 1.5% (T4) and 2.0% (T5) level. Results indicated that body weight gain increased significantly (P<0.05) and feed consumed/g gain decreased significantly (P<0.01) due to inclusion of dried GP in the diet. Further, there was no effect (P>0.05) on carcass yield (g), dressing percent, ready to cook yield (g), meat to bone ratio and percent weight of internal organs. The feed cost / kg gain decreased by ` 2.88 in T2 and 5.71 in T3 while it was increased by 1.20 in T4 and 7.25 in T5 groups as compared to the control (T1). It is concluded that dried GP can be included up to 1.0% level in the diet of quails without any adverse effect.